Impact of the COVID-19 pandemic on mental health of nursing students in Japan: protocol for a cross-sectional study - Jun Kako; Kohei Kajiwara; Masamitsu Kobayashi; Yoshiyasu Ito; Yasutaka Kimura; Takahiro Kakeda; Seiji Hamanishi; Shinsuke Sasaki; Makoto Yamanaka; Hana Kiyohara; Yuki Wakiguchi; Yoji Endo; et al. (BMJ Open)
Introduction The COVID-19 pandemic is spreading globally with a high risk of mortality. It is also significantly affecting mental health. For nursing students, the impact of COVID-19 on mental health is predicted to be significant; however, sufficient data have not been obtained. Therefore, this study will aim to assess the mental health of nursing students and evaluate the related factors.Methods and analysis This proposed study is a cross-sectional survey using a self-report questionnaire. An online questionnaire will be distributed among all nursing students of eight universities in Japan. The survey questionnaire will consist of questions related to demography, life satisfaction, fear of COVID-19, mental health and physical activities. The target sample size is 1300 nursing students. We will calculate descriptive statistics for each measurement item and perform univariate and logistic regression analyses to evaluate the potential risk factors for anxiety, depression and insomnia symptoms in nursing students. The strength of association will be assessed using the OR and its 95% CIs. Statistical significance will be set at a p<0.05.Ethics and dissemination The protocol was approved by the Institutional Review Board (IRB) of the University of Hyogo on 22 March 2021 (ID: 2020F29). In addition, all of the participating facilities required ethical approval from their local IRBs. The findings will be disseminated through peer-reviewed publications and conference presentations. We believe that the proposed large-scale investigation of the mental health of nursing students during the COVID-19 pandemic and the relationship between mental health and fear of COVID-19 are novel and will be a strength of this study.